Defibrillators in general practice. Issue 6455 (17th November 1984) - Clyde, C; Kerr, A; Varghese, A; Wilson, C
Abstract : After a successful pilot scheme introduced in 1975, when six portable defibrillators were provided for health centres, an additional 50 defibrillators were provided in February 1982 for general practitioners to use. Between December 1975 and February 1984 defibrillation was attempted in 54 patients who collapsed with clinical cardiac arrest in the presence of general practitioners or less than five minutes before their arrival. A cardiac output was achieved in 32 patients, 28 survived to reach hospital via a mobile coronary care unit, and 22 were discharged alive. Of the 28 admitted to hospital, 24 were found to have myocardial infarction. If all general practitioners carried defibrillators they might make an important dent in the early mortality from myocardial infarction in addition to that achieved by a mobile coronary care unit.